2012
DOI: 10.4322/apa.2014.058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Antarctic Ozone Hole over South of Brazil in 2010 and 2011

Abstract: e Antarctic Ozone Hole is a cyclical phenomenon, which occurs over the Antarctic region from August to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
1
7
0
11
Order By: Relevance
“…Measurements of total ozone columns (TOCs) have been made around the world by ground-based Dobson spectrophotometer instruments since the 1930s (Dobson, 1930(Dobson, , 1968; recently, more modern automated instruments such as Brewer (Kerr et al, 1985;Kerr, 2002) and SAOZ (Pommereau and Goutail, 1988) spectrophotometers have also been used. Additional techniques such as Fourier transform infrared spectroscopy (FTIR) (Hase et al, 1999), Lidar (Baray et al, 1999), and radiosonde (Thompson et al, 2003) measurements have complemented the continuous record.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of total ozone columns (TOCs) have been made around the world by ground-based Dobson spectrophotometer instruments since the 1930s (Dobson, 1930(Dobson, , 1968; recently, more modern automated instruments such as Brewer (Kerr et al, 1985;Kerr, 2002) and SAOZ (Pommereau and Goutail, 1988) spectrophotometers have also been used. Additional techniques such as Fourier transform infrared spectroscopy (FTIR) (Hase et al, 1999), Lidar (Baray et al, 1999), and radiosonde (Thompson et al, 2003) measurements have complemented the continuous record.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone monitoring through ground-based instruments and comparison with data from satellites for midlatitude regions (Balis et al, 2007;McPeters et al, 1998;Keckhut et al, 2010) is essential because, in these densely populated re-gions, phenomena occur such as the formation of mini ozone holes in the Northern Hemisphere (Semane et al, 2002) and events that influence the Antarctic ozone hole (Farman et al, 1985;Solomon, 1999) in the Southern Hemisphere (Kirchhoff et al, 1996;Perez et al, 1998;De Laat et al, 2010;Pinheiro et al, 2012;Schuch et al, 2015). Ozone content exchange between the stratosphere and the troposphere (Holton et al, 1995;Stohl et al, 2003) occurs in both hemispheres (Škerlak et al, 2014) at midlatitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Perez et al, 2000;Pinheiro et al, 2012, as well as the identification of the existence of a connection between the transport of air masses in the stratosphere and the troposphere weather condition, mainly by the performance of the tropospheric jet stream, where its displacement influence the vertical distribution of ozone content (Bukin et al 2011) and causes intrusion of stratospheric air into the troposphere (Stohl et al, 2003). Moreover, on the South of Brazil, similar to the way the present study, this type of event has occurred after the passage of a frontal system .…”
Section: Discussionmentioning
confidence: 99%
“…The passage of air masses originating from the Antarctic ozone hole (Farman et al, 1985) on medium latitudes was first observed on the South of Brazil (29.4ºS; 53.8ºW) by Kirchhoff et al (1996), being this type of phenomenon called 'influence of the Antarctic ozone hole, which has been frequently observed over South America (Perez et al, 2000;Pinheiro et al, 2012). Peres et al, 2012, observed …”
Section: Introductionmentioning
confidence: 99%
“…Sobre o Sul do Brasil este tipo de fenômeno vem sendo constantemente observado, causando queda temporária média na coluna total de ozônio Pinheiro et al, , 2012, comprovando a importância do tema devido a reduções de 1% no conteúdo de ozônio causarem aumento médio de 1,2% na Radiação Ultravioleta sobre esta região (Guarnieri et al, 2004). Além disso, costumam estar associados a condições de tempo sinóticas na troposfera, principalmente relacionadas a condições pós frontais de massas de ar estáveis .…”
Section: Discussõesunclassified